Study Protocol: Comparison of Clinical Pregnancy Outcomes of Intracytoplasmic Sperm Injection (ICSI) Using Testicular and Ejaculated Spermatozoa in Male Patients with High DNA Fragmentation - Juhi Barai; Akash More; Namrata Choudhary (Journal of Pharmacy and Bioallied Sciences)
Background: This study aims to compare the clinical pregnancy outcome of intracytoplasmic sperm injection (ICSI) using testicular and ejaculated spermatozoa in male patients with high deoxyribonucleic acid (DNA) fragmentation. Patients diagnosed with high DNA fragmentation levels in sperm DNA fragmentation (SDF) tests using sperm chromatin dispersion (SCD) are categorized into two groups one including the male patient undergoing ICSI with ejaculated and another with testicular spermatozoa retrieved via testicular sperm aspiration (TESA). The study evaluates the clinical outcome including fertilization, implantation, and pregnancy rates, comparing the efficacy of testicular versus ejaculated sperm in overcoming the adverse effects of DNA fragmentation. By analyzing ICSI outcomes, the study seeks to establish standardized SDF testing protocols. Objective: The study aims to identify male partners with abnormal semen parameters and evaluate sperm DNA fragmentation (SDF) in both ejaculated and testicular sperm. Additionally, it seeks to assess the effectiveness of the SDF test in detecting DNA damage. Furthermore, the study compares the clinical pregnancy outcomes of ICSI using testicular and ejaculated spermatozoa in male patients with high DNA fragmentation. Methodology: The methodology involves patient consultation, consent, and screening for infections. Semen analysis and DNA fragmentation tests assess sperm quality. For azoospermic patients with high SDF, TESA retrieves sperm for ICSI and normal from ejaculate with high SDF. Outcomes are evaluated for treatment success and DNA integrity. Expected Results: Standardization of the SDF test, in which the best SDF test will be adopted, and a precise threshold will be used to determine the sperm DNA damage which may enhance the ICSI outcome, along with the difference between the ICSI outcome of both the testicular and ejaculated spermatozoa with high SDF. Study Implication: It helps in assessing the ICSI outcome in testicular and ejaculated spermatozoa in patients with high DNA fragmentation.